A systematic review of geopolymer materials: innovations, prevailing constraints and resolutions - Agashua, Lucia Omolayo; Arum, Chinwuba; Oluyemi-Ayibiowu, Bamitale Dorcas; Ikumapayi, Catherine Mayowa (Universitas Mercu Buana, 2024)
Geopolymer is a novel eco-friendly biodegradable cementitious material for which the emergence is expected to reduce the carbon-dioxide emission caused by Portland cement manufacturing companies. Geopolymer material possesses exceptional mechanical properties and other admirable properties such as fire and corrosion resistance. Most industrial solid wastes (ISW) and waste smoldering bottom ash (WSBA) are stacked up, filling land mass, besides their harmful influence on the surroundings. Reprocessing could make them suitable for use as materials for making geopolymers. They can efficiently adsorb heavy metals, dyes or pigments, and other radioactive contaminants, which is very helpful to humanity's future development. On the other hand, due to the exceptional features of geopolymer material, its functions go further than that. Specific helpful information regarding geopolymer materials was made known in this study. The study encompassed the source of geopolymer materials, the geopolymerization process, the categories of activators, their formation techniques, and the diverse usage areas of geopolymer materials. Furthermore, the factors influencing the mechanical features of geopolymer materials were discussed. Finally, these materials' inadequacies and usage precincts were summarized, and their evolution was abridged to prepare a theoretical or hypothetical base for the lasting improvement of geopolymer materials.